Electron Microscopy Imaging of Zinc Soaps Nucleation in Oil Paint. (4th June 2018) - Hermans, Joen; Osmond, Gillian; van Loon, Annelies; Iedema, Piet; Chapman, Robyn; Drennan, John; Jack, Kevin; Rasch, Ronald; Morgan, Garry; Zhang, Zhi; Monteiro, Michael; Keune, Katrien
Abstract: Using the recently developed techniques of electron tomography, we have explored the first stages of disfiguring formation of zinc soaps in modern oil paintings. The formation of complexes of zinc ions with fatty acids in paint layers is a major threat to the stability and appearance of many late 19th and early 20th century oil paintings. Moreover, the occurrence of zinc soaps in oil paintings leading to defects is disturbingly common, but the chemical reactions and migration mechanisms leading to large zinc soap aggregates or zones remain poorly understood. State-of-the-art scanning (SEM) and transmission (TEM) electron microscopy techniques, primarily developed for biological specimens, have enabled us to visualize the earliest stages of crystalline zinc soap growth in a reconstructed zinc white (ZnO) oil paint sample. In situ sectioning techniques and sequential imaging within the SEM allowed three-dimensional tomographic reconstruction of sample morphology. Improvements in the detection and discrimination of backscattered electrons enabled us to identify local precipitation processes with small atomic number contrast. The SEM images were correlated to low-dose and high-sensitivity TEM images, with high-resolution tomography providing unprecedented insight into the structure of nucleating zinc soaps at the molecular level. The correlative approach applied here to study phase separation, and crystallization processes specific to a problem in art conservation creates possibilities for visualization of phase formation in a wide range of soft materials.